MP3 : The Meaning of a Format - Sterne, Jonathan, 1970- (Book collections on Project MUSE., 2012)
Jonathan Sterne shows that understanding the historical meaning of the MP3, the world's most common format for recorded audio, involves rethinking the place of digital technologies in the broader universe of twentieth-century communication history.